DETERMINATION OF SERUM TRACE ELEMENTSMAGNESIUM, COPPER, ZINC, AND SELENIUM IN ASTHMATIC PATIENTS BY ATOMIC ABSORPTION SPECTROPHOTOMETRY - Al-Assaf, Nahla A (Al-Nahrain Journal of Science, 2010)
The aim of this study is to evaluate the levels of trace elements Magnesium (Mg), Zinc (Zn), Copper (Cu), and Selenium (Se) in blood sera of asthmatic patients by Atomic Absorption Spectrophotometry (AAS). The concentrations of Mg, Cu, and Zn have been determined by Flame Atomic Absorption spectrophotometry (FAAS), and Se with flameless Graphite Furnace Atomic Absorption Spectrophotometry (GFAAS). The study involves (55) asthmatic patients as study group and (28) subjects as control from both genders. Serum levels of Mg, Cu, and Se were significantly higher (p<0.001 for all) in patients when compared with healthy subjects, while Zn level was relatively significant (p<0.05). Our observations confirm the efficacy and applicability of (AAS) in determination of trace elements levels in blood sera of asthmatic patients and the effect of these elements in pathogenesis and treatment of the disease.